Patient satisfaction towards pharmacists’ services in the community pharmacies in the Hail region - Tareq Nafea Alharby; Muteb Alanazi; Mukhtar Ansari; Ali Felaih Almutairy; Osama Ayed Altamimi; Saud Talal Jaafari; Saleh Abdulwahab Alassaf; Meshari Khalid Altuwayhir; Faisal Nasser Almutiri; Fahad Saad Aljohani (PLoS ONE, 2026)
Objectives Research on patient satisfaction with community pharmacy services in Saudi Arabia has mostly concentrated on large cities, leaving a significant gap in understanding these services within the Hail region. Evaluating patient satisfaction in Hail is essential to address regional service gaps in privacy and counseling. Thus, this study was designed to assess the patient satisfaction with community pharmacy services in the Hail region. Methods This cross-sectional study targeting the community pharmacy visitors in Hail region was conducted among 200 participants for a duration of three months (i.e., from 14 June 2024–29 September 2024). Patient satisfaction was assessed by a reliable and valid questionnaire. The instrument consisted of 17 items; and all of them were 5-point Likert scale responses (Poor = 1, Fair = 2, Good = 3, Very good = 4, Excellent = 5). To guarantee diverse geographic representation, 20 community pharmacies were purposefully chosen from several Hail City districts. In order to achieve balanced sample across all sites, a total of 200 participants were recruited, with roughly 10 patients joined from each Pharmacy. The data was analyzed for descriptive statistics using the SPSS, version 29.0. Results The majority of the 200 participants in this study (mean age of 37.5 years) were married (60.5%) and male (56.5%). More than half had only completed high school, and only 16% had insurance. Most of the patients (53%) consistently visited the same pharmacy. Pharmacist-patient relationships received the highest level of satisfaction, but accessibility—specifically, the availability of private consultation areas—received the lowest. Regular pharmacy visitors reported higher levels of satisfaction across multiple domains, whereas younger, male, single, better-educated, insured, and healthier patients had more favorable perceptions of medicine availability, highlighting disparities in demographic and health factors. Conclusion The majority of community pharmacy visitors were young adults, married, had a range of educational backgrounds, and frequently used the services without a prescription or health insurance. Overall, patient satisfaction was good; nevertheless, to further improve patient experience and access to pharmacy services, improvements in private consultation facilities and pharmaceutical pricing are required.